In vitro 3D blood/lymph-vascularized human stromal tissues for preclinical assays of cancer metastasis - Nishiguchi, Akihiro; Matsusaki, Michiya; Kano, Mitsunobu R.; Nishihara, Hiroshi; Okano, Daisuke; Asano, Yoshiya; Shimoda, Hiroshi; Kishimoto, Satoko; Iwai, Soichi; Akashi, Mitsuru (Biomaterials, 2018)
Tumour models mimicking in vivo three-dimensional (3D) microenvironments are of increasing interest in drug discovery because of the limitations inherent to current models. For example, preclinical assays that rely on monolayer or spheroid cell cultures cannot easily predict 3D cancer behaviours because they have no vasculature. Furthermore, there are major differences in cancer behaviour between human and animal experiments. Here, we show the construction of 3D blood/lymph-vascularized human stromal tissues that can be combined with cancer cells to mimic dynamic metastasis for real-time throughput screening of secreted proteinases. We validated this tool using three human carcinoma cell types that are known to invade blood/lymph vessels and promote angiogenesis. These cell types exhibited characteristic haematogenous/lymphogenous metastasis and tumour angiogenesis properties. Importantly, these carcinoma cells selectively secreted different matrix metalloproteinases depending on their metastasis stage and target vasculature, suggesting the possibility of developing drugs that can target each secreted proteinase. We conclude that the 3D tissue tool will be a powerful throughput system for predicting cancer cell responses and time-dependent secretion of molecules in preclinical assays. We present a tool for mimicking a series of early metastasis processes including invasion, tumour angiogenesis, intravasation, and extravasation using engineered 3D-blood/lymph-vascularized human stromal tissues. [Display omitted]